Probiotics in the Management of Gingivitis and Periodontitis. A Review - Ulrich Schlagenhauf; Ulrich Schlagenhauf; Yvonne Jockel-Schneider (Frontiers Media S.A., 2021)
In the management of intestinal health problems, the targeted use of probiotic microorganisms is a common therapeutic measure with a long-standing tradition. In clinical dentistry however, probiotics-based therapy is still a rather new and developing field, whose usefulness for the control of gingivitis and periodontitis has been questioned by recent meta-analyses and systematic reviews. The purpose of the subsequent descriptive review is to provide an introduction to the concept of probiotic microorganisms and their multifaceted health-promoting interactions with the human host and microbial competitors, followed by a detailed comparison of the results of available controlled clinical trials assessing the use of probiotics in the control of gingival and periodontal inflammations. It aims at contributing to a deeper understanding of the unique capabilities of probiotics to resolve chronic plaque-induced inflammation even in the absence of mechanical plaque control and will discuss how possible misconceptions about the rationale for using probiotics may have led to the present controversies about their usefulness as a therapeutic option.